2013
DOI: 10.1513/annalsats.201301-007oc
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Healthcare Use in a Randomized Controlled Lung Cancer Screening Study

Abstract: Rationale: Understanding the quality of life of lung cancer screening program participants, and the impact of program participation on quality of life and healthcare use, will help in the assessment of the value of screening.Objectives: Determine the quality of life of participants in a lung cancer screening study and assess the effect of an abnormal screening finding on quality of life and healthcare use.Methods: Quality-of-life measures and data on the use of healthcare services were collected prospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…3,710,24,25 Yet, our results differ somewhat from the literature on the impact of screen-detected pulmonary nodules. 15,2628 Some lung cancer screening trials do suggest that patients experience mild short-term distress, 15 anxiety, 29 or impairments in quality of life 30 after nodule detection. But in the National Lung Screening Trial (the largest study of lung cancer screening), there was no significant change in anxiety or quality of life among patients with a screen-detected nodule, compared to those with normal screening tests.…”
Section: Discussionmentioning
confidence: 99%
“…3,710,24,25 Yet, our results differ somewhat from the literature on the impact of screen-detected pulmonary nodules. 15,2628 Some lung cancer screening trials do suggest that patients experience mild short-term distress, 15 anxiety, 29 or impairments in quality of life 30 after nodule detection. But in the National Lung Screening Trial (the largest study of lung cancer screening), there was no significant change in anxiety or quality of life among patients with a screen-detected nodule, compared to those with normal screening tests.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Such tracking systems have been recommended as a critical component of highquality screening programs, 32 along with establishment of registries. 9 Development of both should include methods to improve patient-centered care. In addition to tracking systems, high-quality patient-clinician communication may improve patient adherence to follow-up recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] Although some patients enrolled in lung cancer screening trials have shown an increase in negative psychosocial outcomes such as distress and anxiety, fi ndings are inconsistent. [8][9][10] Among patients with incidentally detected nodules in routine clinical settings, distress seems to be common and occasionally severe. [11][12][13][14] Patients who have been notifi ed about incidental lung nodules have inadequate knowledge about what nodules are, the causes, the risk a nodule could be cancer, and the follow-up plan.…”
mentioning
confidence: 99%
“…The average odds ratios of early diagnosis in programme designs were predicted to be 2. [27] Probability someone responds to the initial invite and returns the questionnaire 0.307 UKLS trial [6] Probability someone joins screening programme given they are eligible 0.465 UKLS trial [6] Sensitivity of low-dose CT test for lung cancer 0.709 UKLS trial [6] Specificity of low-dose CT test for lung cancer 0.624 UKLS trial [6] Utility of male smoker in the UK general population/occult lung cancer 0.7816 Health Survey for England [27] Utility of female smoker in the UK general population/occult lung cancer 0.7531 Health Survey for England [27] Disutility associated with a false-positive screen − 0.063 Mazzone et al [30] Disutility associated with anxiety of a screening event − 0.010 NELSON trial [29] Duration of disutility from false-positive screen 3 months Assumption…”
Section: Secondary Health Outcomesmentioning
confidence: 99%